Environmental factors associated with freshwater recreational water quality in Niagara Region, Ontario, Canada: A path analysis. (22nd September 2021) - Sanchez, J. Johanna; Young, Ian; Heasley, Cole; Kelly, Jeremy; Habjan, Anthony; Waterhouse, Ryan; Tustin, Jordan
Abstract: Escherichia coli concentration levels in recreational water are used by beach managers to evaluate the risk of gastrointestinal illness among beachgoers. We examined the relationship between specific environmental factors and E. coli concentration in recreational beaches in the Niagara Region. We analysed E. coli geometric means collected from eight beaches from two of the Great Lakes in the Niagara Region in Ontario, between 2011 and 2019. We applied path analysis to evaluate the relationship between the environmental factors and E. coli concentrations, including whether effects were direct or indirect via a mediator. Turbidity was found to be an important mediator for the indirect effect of environmental variables overall and in beach-specific models. Rainfall and streamflow had a positive indirect effect on E. coli via turbidity and a direct effect in five out of seven beach models. Streamflow was also a mediator for the indirect effect of previous day air temperature in five out of seven models. In three subset models, outfall E. coli concentration was a mediator for the effect of the environmental factors. Using a novel methodological approach, this study identifies important relationships and pathways that predict beach E. coli concentration in freshwater beaches located on two of the Great Lakes.